(untitled) (African Journal of Biomedical Research, 2022)
This study analyses generation and composition of biomedical waste in selected hospitals in Akure local government area, Nigeria. Cross sectional survey research design was adopted, and both primary and secondary data were sourced. A multi-stage sampling technique was used. Of the 18 local government area in Ondo state, Akure South Local Government Area was purposively selected. About 8 out of the entire 147 health care facilities (4 private and 4 public) identified were randomly selected representing 11% of the sample frame. Data were analyzed using both descriptive and inferential (ANOVA) statistics. All the data were validated at P value _< 0.05. The findings revealed that Healthcare facilities generate more of sharps (338.1kg) and infectious (367kg) waste. All (100%) the facilities composed of sharp, infectious, non-risk forms of biomedical waste (12.5%) and chemical waste. Conclusively, there is variation in the biomedical waste generation, therefore effective waste management strategies should be adopted.